2006
DOI: 10.1128/aac.00007-06
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Gene Cluster for the Polyenoyltetramic Acid α-Lipomycin

Abstract: The gram-positive bacterium Streptomyces aureofaciens Tü117 produces the acyclic polyene antibiotic ␣-lipomycin. The entire biosynthetic gene cluster (lip gene cluster) was cloned and characterized. DNA sequence analysis of a 74-kb region revealed the presence of 28 complete open reading frames (ORFs), 22 of them belonging to the biosynthetic gene cluster. Central to the cluster is a polyketide synthase locus that encodes an eight-module system comprised of four multifunctional proteins. In addition, one ORF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 51 publications
1
58
0
4
Order By: Relevance
“…We expected the same to be true for the frontalamides. These expectations were further bolstered by the observation that bacterial tetramic-acid polyketides such as α-lipomycin are produced by modular PKS and NRPS enzymology, requiring multiple PKS enzymes (23). However, genome searches in the vicinity of ftd clusters revealed no juxtaposed PKS genes and left unresolved the issue of how the remainder of the frontalamide/HSAF-type backbone is biosynthesized.…”
Section: Resultsmentioning
confidence: 99%
“…We expected the same to be true for the frontalamides. These expectations were further bolstered by the observation that bacterial tetramic-acid polyketides such as α-lipomycin are produced by modular PKS and NRPS enzymology, requiring multiple PKS enzymes (23). However, genome searches in the vicinity of ftd clusters revealed no juxtaposed PKS genes and left unresolved the issue of how the remainder of the frontalamide/HSAF-type backbone is biosynthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Hence we turned to the lipomycin PKS, which was proposed to use isobutyryl-CoA to initiate α-lipomycin biosynthesis, and whose AT-ACP loading didomain is linked to module 1 to form the first polypeptide (LipPks1) of the PKS complex ( Figure 1a). 8 In our hands, linkage of lipPKS1 to the erythromycin PKS thioesterase (TE) gave rise to soluble, active protein (LipPks1+TE) in E. coli. One of the key findings in our analysis was an unexpected substrate profile of the loading AT domain of the lipomycin PKS (Figure 1b).…”
Section: Substrate Specificities Of Pks Domainsmentioning
confidence: 92%
“…One of the key findings in our analysis was an unexpected substrate profile of the loading AT domain of the lipomycin PKS (Figure 1b). 8,9 AT domains of type I PKSs are the primary determinants of building block specificity in polyketide biosynthesis. Previously, in vitro kinetic studies of the loading AT domain of the erythromycin PKS revealed its specificity for propionyl-CoA, although acetyl-and butyryl-CoA were also accepted as substrates with about 40-fold lower k cat /K M .…”
Section: Substrate Specificities Of Pks Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we turned to the lipomycin PKS, whose loading acyltransferase (AT) domain shares 50% amino acid similarity with the avermectin loading AT. 9 Unlike the avermectin PKS, the first protein of the lipomycin PKS (LipPks1) contains only the loading didomain and module 1, and linkage of LipPks1 to the erythromycin PKS TE domain Figure 2 Biosynthesis of erythromycin (a) and tiacumicin (b). Schemes for the step-wise biosynthesis of the polyketide backbones of 6-deoxyerythronolide B (6-dEB) and tiacumicinone showing the structure of the intermediate tethered to the acyl carrier protein (ACP) after all reactions by the modular domains are complete.…”
Section: Introductionmentioning
confidence: 99%